The Rights-Based Labor Law: A Comparison of Indonesian and Nepal Policies - Rahayu, Devi; Munir , Mishbahul; Wartiningsih; Shokhikhah, Zilda Khilmatus; Thapa, Nar Yan (Universitas Negeri Surabaya, 2025)
Human Rights (HR) serve as a crucial foundation in labor policies to protect workers' rights. However, both Indonesia and Nepal face significant challenges in their implementation, such as rights violations in the informal and formal sectors in Indonesia, and the risk of exploitation of Nepali migrant workers, exacerbated by the pandemic, weak oversight, and a lack of social protection. This study aims to analyze the differences in the implementation of human rights-based labor laws in Indonesia and Nepal and to identify the factors influencing the success or challenges of their enforcement. The study employs a normative legal method with legislative, comparative, conceptual, and historical approaches to analyze the integration of human rights principles into labor policies in Indonesia and Nepal. It relies on qualitative data from library research, including primary, secondary, and tertiary legal materials. The findings reveal that the implementation of human rights-based labor laws in Indonesia and Nepal demonstrates a commitment to international principles through the ratification of ILO conventions. However, both countries face distinct challenges within their social, economic, and implementation capacities. Indonesia focuses on protecting minimum wages, social security, and regulating working hours but struggles with gender discrimination and issues in the informal workforce. Meanwhile, Nepal deals with caste discrimination, migrant worker protection, and inadequate social security schemes. Both countries encounter oversight challenges, but factors such as socio-economic context, pro-investment policies, and commitment to international standards influence the success and challenges of implementing human rights-based labor laws in these two nations.